2009
DOI: 10.1017/s1368980008003534
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the evolution of BMI in Belgian army men

Abstract: Objectives: The first aim was to evaluate BMI cross-sectionally over a period of 14 years (1992 to 2005) in 43 343 army men and the second was to compare BMI using the paired data of 1497 army men. The data were analysed as a function of the military ranking system, used as an indicator for socio-economic position. Design: Multiple cross-sectional and longitudinal design. Results: A significant increase of BMI between age categories was detected over the 14-year period; BMI remained stable in each age categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Across both genders, age represented a clear relationship with obesity and risk to obesity-related diseases. This relationship is generally supported in other studies on the military population (Bray et al, 2009;Helmhout, 2009;Mullie et al, 2008;Napredit et al, 2005;Shaw et al, 2013). Similarly a significant association, 2 (3) ¼ 41.86 (p50.05), was found between age group and BMI classification of UK Royal Navy personnel, whereby participants in the 35-44 and 45 year age group were more likely to be obese in comparison to the younger age groups (Shaw et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Across both genders, age represented a clear relationship with obesity and risk to obesity-related diseases. This relationship is generally supported in other studies on the military population (Bray et al, 2009;Helmhout, 2009;Mullie et al, 2008;Napredit et al, 2005;Shaw et al, 2013). Similarly a significant association, 2 (3) ¼ 41.86 (p50.05), was found between age group and BMI classification of UK Royal Navy personnel, whereby participants in the 35-44 and 45 year age group were more likely to be obese in comparison to the younger age groups (Shaw et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…However, the higher levels of obesity that were observed in the LE cohort either became insignificant (female) or reduced in significance (male) and effect size, when the predictor variables were controlled for each other. Two studies on military populations have reported elevated levels of obesity in the soldier populations as opposed to the officer populations (Bray et al, 2009;Mullie et al, 2008). One recent study indicated that a correlation might exist between the hierarchical system of rank employed within the military and 'pay-group', with higher rank commanding higher pay (Sanderson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratification in normal weight, overweight and obesity did not influence the relation between socioeconomic indicator and dietary pattern. Although socioeconomic differences in prevalence of obesity have been described, that is, higher prevalence for the lowest socioeconomic positions (Mullie et al, 2008), dietary pattern analysis seems not to be able to detect a specific dietary pattern explaining this socioeconomic occurrence of obesity. The positive association between socioeconomic position and dietary pattern has been confirmed by research carried out on different populations, using different indexes or statistical techniques to determine dietary patterns.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, testing the weight gain hypothesis in specific populations can help to clarify the relationship with secular BMI increase. An increasing prevalence of adiposity has been described in military populations, which can negatively influence military readiness 17. When relating dietary pattern to weight gain, the clear socioeconomic stratification of a military population can be of added value to investigate the relation between socioeconomic status and nutrition.…”
Section: Introductionmentioning
confidence: 99%